Análisis de las cargas no lineales y su incidencia en la generación de armónicos en la cámara eléctrica del tren de laminación dos de la empresa novacero s.a. en el periodo 2016-2017. Diseño de filtros armónicos impares en baja tensión para mejorar la calidad de energía eléctrica - Velásquez Tapia, Jorge Aníbal (2017)
In the present job, the purpose is design Odd harmonic filters in low voltage, for the mitigation of harmonics to improve the quality of the electrical energy. As experimental installation it was taken non-linear loads which feed the Tansformer Westinghouse of the electrical camera in the rolling mill number two in the NOVACERO S.A factory during the period 2016-2017. Through of a network analyzer Circutor AR6 it is measured the signal distortion taking account both voltages as the current to an adequate characterization of the harmonics produced by this circuit under study. Knowing the most representative harmonic It is determine the method of design of the passive tuned filter taking account the order of the harmonics, The magnitude, nominal voltage and appropriate power. With the getting values in the filters design it’s done a simulation in the Easy Power software. Corroborating the waited performance in the design, with the getting and analyzing results presents conclusions based on the same results.